Making sense of Psalm 127:3-5 in African / South African contexts - Masenya, Madipoane (Old Testament Essays, 2019)
African wisdom sayings have enjoyed and continue to enjoy some authoritative status in varying African contexts from time immemorial till today. As sacred texts, African proverbs have shaped and continue to shape, whether consciously or not, the worldview of African peoples, even in present day contexts. The holistic worldview which embeds Ps 127:3-5, one that underlies many an African proverb, reveals the great store set by large families and the celebration of women’s role as mothers in both contexts. The main question that this article seeks to engage is: If read from an (African) South African context, which insights may emerge from Ps 127:3-5?
free